Моделирующая установка по определению адгезионной составляющей силы трения в процессе резания материалов - Маршуба, Вячеслав Павлович; Плахотникова, Инна Борисовна; Маршуба, О. В. (НТУ "ХПИ", 2008)
Determination of substantive provisions, methods of researches of mechanical and adhesive constituent of force of friction in the process of cutting of different materials. Taking for basis the developed method of researches of constituents of force of friction, and also existent conformities to the law of cooperation of the physical phenomena arising up and flowing in the process of cutting, to create the physical and mathematical model of process of formation of growths on the basis of the explored mechanism of mechanical and adhesive constituent of force of friction.
Keywords: инструмент режущий; стружка; напряжение контактное; нарост; сверление глубокое; модель физическая; модель математическая; прочность тангенциальная; момент крутящий; динамометр